PENERAPAN GROUP INVESTIGATION PADA PEMBELAJARAN SAINS UNTUK MENGEMBANGKAN KARAKTER SISWA SMP KELAS VIII (UPEJ Unnes Physics Education Journal, 2012)
This action research aims to develop character and improve students learning outcomes through the implementation of Group Investigation in science learning. This research was done in three cycles, consist of planning, action, observation and reflection. Steps of the lesson is students make a groups,every groups consist of 5 to 6 students, discuss their plan and conduct an investigation, and then prepared a report on the results of the investigation to be presented in the classroom followed by evaluation at the end of the lesson. The data about students character development obtained from observation sand questionnaire. Cognitive learning outcomes were collected from evaluation test while the psycomotor learning outcomes obtained by observation sheet. The results of cognitive, psychomotor and character of the students were analyzed using gain test. Results of this research shows that the application of Group Investigation in science can develop honest, discipline, curiosity, creative and communicative characters of students Class VIIIA SMPN 2 Sumber , Rembang. The increase from the first cycle to the second cycle is 0.20 and from II to III is 0.28. In addition to the characters, cognitive and psychomotor learning outcomes of students also increased each cycle.